Methodological basis of management of diversification and integration development of enterprises in conditions of non-technological reproduction - Zalutska, Khrystyna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The complexity, dynamicity, and unexpectedness of conditions for functioning of contemporary enterprises strengthen requirements to effectiveness of their activities. This process demands for searching new directions of development. The efficient implementation of these directions stipulates the necessity for forming the specific methodology for managing such development based on peculiarities of existing conditions. A subject of the scientific article is the methodology for managing the development of an enterprise under the neo-technological reproduction. A purpose of research is to form the methodology for managing the diversification integrational development of an enterprise under the neo-technological reproduction grounded in the mutually reinforced unity of methodologies for the cognition, practical value, and evaluation. To achieve the purpose, the author has done the research by applying the following methods: analogy; abstraction; grouping; comparison, system analysis. The author suggests and proves the expediency of forming the methodology for managing the diversification integrational development of an enterprise under the neo-technological reproduction grounded in the mutually reinforced unity of methodologies for the cognition, practical value, and evaluation. The author substantiates the mutually reinforced influence of the main aspects of forming each of the indicated methodologies. The author describes peculiarities of building each of the methodologies, taking into account the content, structure, and purpose of their key elements under contemporary conditions of development. The author proves that development of a disciplinary paradigm depending on the level of complexity of the examined issues and ways managers can solve them is the ground for the mutually reinforced unity of the considered methodologies. The suggested approach to forming the methodology for managing the diversification integrational development of an enterprise under the neo-technological reproduction enables to determine and ensure the integrity of enterprise’s processes at the expense of managerial decisions made in accordance with the evaluation, which maximally takes into account relevant, accurate, and systematized information on processes and phenomena as the basis for up-to-date knowledge and views on managing the development of an enterprise under the neo-technological reproduction.